An Empirical Analysis of the Impact of Supply Chain Strategy and Organizational Structure on Operational and Financial Performance - Phuanerys , Sharon (American Journal of Business Science Philosophy, 2025)
Indonesia has encountered significant economic challenges indicated by the mass closure of major factories in Indonesia, which are related to the current issue, such as global supply chains, logistics, declining sales, and due to the company's reliance on outdated supply chain methodologies. This research will examine and investigate the relationship between supply chain strategy, organizational structure and operational performance on financial performance based on 153 respondents sample data that has been collected through questionnaires. The data was analyzed using PLS-SEM through SmartPLS 4.0 software. The findings of this study indicate the nonexistence of a direct effect on supply chain strategy and organizational structure towards the financial performance and the relationship between supply chain strategy and operational performance is also not supported. However, organizational structure is found to influence operational performance and has a direct effect on financial performance. It is also revealed that the operational performance has a significant positive mediating effect on the relationship between organizational structure and financial performance. The results shows that external factors like competition, the US-China trade war, the pandemic’s long-term impact and the parent company’s decision play a major role for the decline in Indonesia companies operational and financial performance.
Keywords: supply chain strategy; organizational structure; operational performance; financial performance